1999
DOI: 10.1017/s1368980099000178
|View full text |Cite
|
Sign up to set email alerts
|

Variables independently associated with self-reported obesity in the European Union

Abstract: Objective: The rapid increase in obesity rates over recent years suggest that cultural and societal influences are affecting the adjustment in the energy balance equation in addition to other physiopathological or genetic determinants. Therefore, a pan-EU study was carried out to explore the influence of sociodemographic factors as well as some attitudes (smoking and exercise) on the prevalence of obesity in the adult population of all 15 member states of the EU. Design: Overall, a sample of 15 239 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
104
2
16

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 43 publications
19
104
2
16
Order By: Relevance
“…Our estimates of overweight and obese subjects are in broad agreement with a survey conducted in 2003 on more than Overweight and obesity in Italy S Gallus et al confirm the findings from a survey including more than 15 000 adults from the 15 countries of the former European Union (Martinez et al, 1999), showing that Italy, with France and Luxembourg, had the lowest prevalence of overweight or obese adults (37% as compared to an average of 41% for the European Union) (Martinez et al, 1999). Several other surveys from European countries confirmed the relatively favourable situation in Italy in terms of obesity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our estimates of overweight and obese subjects are in broad agreement with a survey conducted in 2003 on more than Overweight and obesity in Italy S Gallus et al confirm the findings from a survey including more than 15 000 adults from the 15 countries of the former European Union (Martinez et al, 1999), showing that Italy, with France and Luxembourg, had the lowest prevalence of overweight or obese adults (37% as compared to an average of 41% for the European Union) (Martinez et al, 1999). Several other surveys from European countries confirmed the relatively favourable situation in Italy in terms of obesity.…”
Section: Discussionsupporting
confidence: 91%
“…As it was shown in several developed countries, including Western European countries (Seidell and Flegal, 1997;Sundquist and Johansson, 1998;Martinez et al, 1999;Sarlio-Lahteenkorva and Lahelma, 1999;Aranceta et al, 2001;Tur et al, 2005), the USA (Freedman et al, 2002), but even in the developing world with a comparatively high gross domestic product (Sibai et al, 2003;Monteiro et al, 2004), prevalence of overweight and obesity was inversely associated with levels of education. Therefore, in Italy, lowereducated categories have an unfavourable pattern not only in terms of smoking prevalence (Gallus et al, 2006), but also in terms of obesity.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A study that used a large sample of EU citizens also revealed educational level to have a stronger association with obesity than surrogate measures of occupational class (8) .…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%